DNA-mediated gene transfer: recombination between cotransferred DNA sequences and recovery of recombinants in a plasmid. - Anderson, R A (1982)
Ltk- aprt- mouse L cells were transformed to the tk+ phenotype with 10 ng of the herpes simplex virus-1 thymidine kinase (tk) gene and 20 micrograms of pBR322 or simian virus 40 (SV40) DNA. DNAs from five cloned cell lines show restriction endonuclease fragments that hybridize to both tk and pBR322 or SV40 DNA. In all of the cell lines some of these fragments also contain cellular DNA sequences. The use of carrier DNAs with defined sequences has enabled us to demonstrate that the joining of carrier and selectable gene sequences occurs in mouse cells. In one case we have been able to use the ampicillin resistance marker of pBR322 to "rescue" a recombinant plasmid. An analysis of the junction between pBR322 and tk in this plasmid suggests that a small area of homology (16 of 19 base pairs) might be involved in the recombination process.